Eligibility of patients with peripheral arterial disease for participation in a community-based walking exercise program: a single-centre experience - Müller-Bühl, Uwe; Engeser, Peter; Leutgeb, Rüdiger; Szecsenyi, Joachim (International angiology, 2012)
AIM: Eligibility of patients with peripheral arterial disease (PAD) for exercise therapy is the most important requirement for predicting their training group adherence. METHODS: In this prospective, exploratory study over a period of 1 year, a total of 462 PAD patients of an angiological outpatient routine care setting were consecutively recruited to the study. As non-eligibility criteria for exercise therapy were defined: resting pain or gangrene (Fontaine stage III and IV PAD), the inability to complete treadmill exercise, or premature treadmill discontinuation due to non-vascular walking pain. Also, PAD patients without subjective walking limitation (Fontaine stage I PAD) were assessed as unwilling, i.e. non-eligible for exercise training adherence. Criterion for patients eligibility was the occurrence of intermittent claudication on treadmill test (Fontaine stage II PAD). RESULTS: A total of 346 patients (age median 71 years, males 58.5%) were candidates for conservative therapy. Of them, 166 subjects (48%) were assessed as eligible for participation in walking exercise program. 180 of the patients (52%) were deemed as non-eligible to perform walking exercise therapy. 115 patients (33%) were physically limited by critical limb ischemia (Fontaine stage III and IV PAD), severe comorbid cardiovascular disease or orthopaedic disorder. In 65 PAD patients (19%) the subjective walking capacity was not restricted. Social, logistical or other factors were found in 27 patients (8%) to be barriers for exercise training commencement. CONCLUSION: In half of the PAD patients whose attendance in a community-based walking exercise program would be a therapeutically reasonable activity, a range of vascular and non-vascular factors are obstacles for participation. Further research is needed to investigate what measures might enhance the proportion of exercise therapy participants.